Possible anti-fouling effect of polyenes in molluscs shell - Maksim Karpenko; Alexander Karpenko; Vyacheslav Odintsov (Annals of Limnology and Oceanography - Peertechz Publications, 2024)
Polyenes were analysed in two species of marine gastropods (the periwinkles Littorina brevicula and Littorina mandshurica) and two species of marine bivalves (the mussels Mytilus trossulus and Crenomytilus grayanus) to determine the relationship of these compounds with the fouling of molluscs shell. It was found that the shells of the Littorina gastropods and M. trossulus, which are rarely overgrown by fouling organisms in nature, contained polyenes. In rare cases of fouling by Balanus barnacles, there were no polyenes at the sites of their attachment on the shells. Polyenes were not found in the shells of C. grayanus, which are often prone to fouling. The role of polyenes in the possible anti-fouling properties of molluscan shells is discussed.